PERANCANGAN SISTEM PEMESANAN KATERING BERBASIS WEB PADA KATERING VIONA BEKASII - Siti Nurmiati; Helasdi Cakrawali (JURNAL REKAYASA INFORMASI, 2023)
The development of information, communication and technology (Wanda Kurniawan, 2020) is very rapid and the use of technological developments can be seen as one of the right answers to overcome various problems problems in various fields (Siti Nurmiati G. A., 2021) (Siti Nurmiati G. A., 2022). One of the factors supporting the success of a company using technology (Siti Nurmiati A. S., 2019) in this case is a web-based catering ordering system. (Tri Wulandari, 2022) with a system design approach using UML (Unified Modeling Language) which consists of use case diagrams and activity diagrams. Activity Diagram consists of activity login, registration, add categories, add products, orders, administrators, print reports. Keywords : Techology, Information, Use Case Diagram, Activity Diagram